STRATEGI PENGELOLAAN ASET TETAP PADA PEMERINTAH PROVINSI BANTEN - Mulyani, Een; Rachmina, Dwi; Kusnadi, Nunung (Program Studi Manajemen Pembangunan Daerah. Fakultas Ekonomi dan Manajemen. IPB University, 2016)
The Government of Banten Province during the years 2011-2014 has not received an Unqualified Opinion (WTP) of The Supreme Audit Agency (BPK) in its financial statements. The opinion had been given by BPK during the years of 2011-2012 is The Qualified Opinion (WDP). The opinion for years of 2013-2014 is Disclaimer Opinion (TMP).The key to giving WDP and TMP, among others, for the presentation of assets are considered not meet the principles of fairness appropriate presentation of The Government Accounting Standards (SAP). The research objective to describe fixed asset management system. The results of the performance of the system in the form of presentation of fixed assets. The next goal to identify internal and external factors affecting fixed asset management system. The ultimate destination for formulating strategies to improve management of fixed assets. The study was conducted in The Government of Banten Province, particularly the Bureau of Equipment and Assets (BPA) under the Regional Secretary and all work units (SKPD). Methods for assessing the performance of the presentation of fixed assets is Transformation Index. Identification of factors that affect the management of assets and formulate a strategy used SWOT Analysis Method. Methods of Analysis Hierarchy Process (AHP) to ge the priority of a strategy based on expert opinion. Conclusion the study shows the priority of asset management strategy is a strategy to improve the quality of data assets, strategy implementation Improvement Action Plan (RTP) and strategies for improving inter-agency cooperation. The formulation of the strategy is also supported by the proposed program of each strategy. The results of the study are expected to improve fixed asset management system and its implementation in The Government of Banten Province.Key words: financial statement, fixed asset, strategy ABSTRAK Pemerintah Provinsi Banten selama tahun 2011-2014 belum memperoleh opini Wajar Tanpa Pengecualian (WTP) dari Badan Pemeriksa Keuangan (BPK) pada laporan keuangannya. Opini yang diberikan oleh BPK untuk tahun 2011 dan 2012 adalah Wajar Dengan Pengecualian (WDP). Opini untuk tahun 2013 dan 2014 berupa Tidak Menyatakan Pendapat (TMP). Kunci dari pemberian opini WDP dan TMP antara lain karena penyajian aset tetap dianggap belum memenuhi prinsip kewajaran penyajian sesuai Standar Akuntansi Pemerintah (SAP). Tujuan penelitian ini adalah untuk mendeskripsikan sistem pengelolaan aset tetap. Hasil dari sistem berupa kinerja penyajian aset tetap. Tujuan berikutnya mengidentifikasi faktor internal dan eksternal yang mempengaruhi sistem pengelolaan aset tetap. Tujuan terakhir untuk merumuskan strategi perbaikan pengelolaan aset tetap. Penelitian dilakukan pada Pemerintah Provinsi Banten, khususnya Biro Perlengkapan dan Aset (BPA) di bawah Sekretaris Daerah beserta seluruh Satuan Kerja Perangkat Daerah (SKPD). Metode untuk menilai kinerja penyajian aset tetap adalah Transformasi Indek. Identifikasi faktor-faktor yang mempengaruhi pengelolaan aset dan merumuskan strategi digunakan Metode Analisis SWOT. Metode Analisis Hierarchy Process (AHP) membantu pemilihan prioritas strategi berdasarkan pendapat ahli. Kesimpulan penelitian menunjukkan prioritas strategi pengelolaan aset adalah strategi peningkatan kualitas aset data, strategi pelaksanaan Rencana Tindak Perbaikan (RTP)/action plan dan strategi peningkatan kerjasama antar lembaga. Perumusan strategi juga ditunjang dengan usulan kebijakan/program terhadap masing-masing strategi. Hasil dari penelitian diharapkan dapat memperbaiki sistem pengelolaan aset tetap dan pelaksanaannya di Pemerintah Provinsi Banten.Kata Kunci: Laporan Keuangan, Aset Tetap, Strategi